Increased Subjectivity in Audio Description of Visual Art: A Focus Group Reception Study of Content Minimalism and Interpretive Voicing - Silvia Soler Gallego; Luque Colmenero, María Olalla (Journal of Audiovisual Translation, 2023)
This article discusses a focus group reception study of visual art audio description (AD) that focuses on the standard style as described in previous corpus-based studies, along with one of the less frequent approaches also found among current practices, namely the “gist” style. The results from the qualitative analysis of the focus group discussions show that user experience of the gist AD style varies among participants, with some reporting positive impressions thereof. In addition, users’ experience of AD has several layers, since the discussions progressed from specific aspects to broader questions dealing with the very definition of AD and user preferences regarding visual arts. Lay Summary This article talks about a research study that looked at how people perceive audio descriptions (AD) in visual art. Audio description is a way of providing information about visual elements for individuals who are blind or visually impaired. The study focused on two styles: the standard style, which is commonly used and has been studied before, and a less common approach known as the "gist" style. The gist style is type of AD where only a few visual components are mentioned without many conceptual connections between them and with high importance to the voice and it modulations. The researchers conducted focus group discussions to understand how participants experienced these different AD styles. These discussions are group conversations where participants share their opinions and experiences about a particular topic, guided by a moderator. The results were obtained through qualitative analysis, where the focus is on understanding people's experiences and opinions in-depth, often involving open-ended discussions rather than quantitative data. They revealed that people had varying opinions about the gist style. Some participants liked it, while others didn't. Moreover, the discussions went beyond just talking about specific aspects of AD; they delved into broader questions about what AD is and what users prefer when it comes to describing visual art. The study found that opinions on the gist style varied among participants, and the discussions went beyond specific details of AD to explore broader questions about its definition and user preferences in the context of visual arts.